Telaah Historis-Hermeneutis Hadis-Hadis Tentang Ayah - Hardivizon Hardivizon (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
This study aims to find new meanings of hadiths regarding fathers, especially on the theme of: 1) the prohibition against hating fathers; 2) fathers entitled to the property of their children; 3) fathers as well as possible the gates of heaven. The side of study is the authenticity and meaning of the hadith. The approach that used in this study is hermeneutics offered by Hassan Hanafi in understanding the text of revelation as a source of law. Namely by building three consciousnesses; historical, eidetic, and praxis. This study found that in terms of quality, the three hadiths were in the position of maqbul, which could be accepted as proof. In meaning, it is understood that the role of a father in his child’s life is very importance. Hating father is the result of making a child fall into kufr. No matter how bad the condition of a father, children should not hate or not admit him. The threat of a big sin was given by the Prophet to the person who did it. Child service must also be realized in the form of compensation for the father. Father's glory is symbolized as the best door of the heaven for the child.